Peran Pemanfaatan SIA Sebagai Variabel Moderasi Terhadap Pengaruh Antara Pelatihan dan Kualitas Pencatatan Akuntansi pada UMKM Batik di Kabupaten Sragen - Luviana, Riswanda; Sarwono , Aris Eddy (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This research aims to examine how financial training affects the quality of accounting records, with the use of accounting information systems acting as a mediating variable among batik micro, small, and medium enterprises (MSMEs) in Sragen Regency. One of the main challenges encountered by batik MSMEs is the inadequate quality of their accounting records, which limits the reliability of financial information for informed business decision-making. The study adopts a quantitative design using a survey approach. Primary data were obtained through questionnaires distributed to batik MSME owners as respondents. Data were analyzed using regression analysis, path analysis, and the Sobel test to assess the mediating effect of accounting information system utilization. The findings reveal that financial training has a significant impact on both the adoption of accounting information systems and the quality of accounting records. Moreover, the utilization of accounting information systems is empirically shown to mediate the relationship between financial training and the quality of accounting records. These results imply that enhancing the scope and effectiveness of financial training programs can motivate MSME owners to implement accounting information systems more optimally, leading to financial records that are more accurate, relevant, and dependable. This study offers practical insights for stakeholders in formulating financial training initiatives to strengthen financial management practices within MSMEs.